IMPACT OF ICT IN DISTANCE EDUCATION AND TEACHER PERCEPTION TOWARDS KNOWLEDGE OF ICT TOOLS - Gupta, Rajendra (International Journal of Research -GRANTHAALAYAH, 2017)
The Information and Communication Technology (ICT) can be one of the important tools while teaching at under graduate and post graduate level. It is being popular at education sector because of their different modes of operations. Since, the education includes regular, online, distance and part time education, so there are a number of applications based on ICT are available in the real world. In this paper, the emphasis is given on the use of ICT by teachers and its effects on the teaching methods with their different perspectives. The paper has also focused on the certain important issues related to the effective implementation of ICTs at educational level and provides suggestions for effectively use of ICT at higher education level for distance education.